A case of spindle cell squamous cell carcinoma of the tongue complicated by verrucous carcinoma - Yusuke Matsuzaki; Daiki Saito; Saimon Yasuhara; Yukio Watabe; Shiro Shigematsu (Oral Oncology Reports)
We report herein a highly unusual case of spindle cell squamous cell carcinoma (SCSCC), a rare form of oral cancer, co-occurring with verrucous carcinoma. The patient, a 57-year-old male, presented with a tongue lesion with macroscopic features resembling those of a cancerous ulcer and verrucous carcinoma. Histological examination of a biopsy specimen led to the diagnosis of the lesion as SCSCC. The lesion was treated with a surgical resection and chemotherapy. The present case underscores the importance of bearing the possibility of spindle cell carcinoma in mind when assessing a tongue lesion which was initially diagnosed as verrucous carcinoma.